Colloidal Synthesis and Optical Properties of All‐Inorganic Low‐Dimensional Cesium Copper Halide Nanocrystals. (24th September 2019) - Cheng, Pengfei; Sun, Lei; Feng, Lu; Yang, Songqiu; Yang, Yang; Zheng, Daoyuan; Zhao, Yang; Sang, Youbao; Zhang, Ruiling; Wei, Donghui; Deng, Weiqiao; Han, Keli
Abstract: Low‐dimensional metal halides have recently attracted extensive attention owing to their unique structure and photoelectric properties. Herein, we report the colloidal synthesis of all‐inorganic low‐dimensional cesium copper halide nanocrystals (NCs) by adopting a hot‐injection approach. Using the same reactants and ligands, but different reaction temperatures, both 1D CsCu2 I3 nanorods and 0D Cs3 Cu2 I5 NCs can be prepared. Density functional theory indicates that the reduced dimensionality in 1D CsCu2 I3 compared to 0D Cs3 Cu2 I5 makes the excitons more localized, which accounts for the strong emission of 0D Cs3 Cu2 I5 NCs. Subsequent optical characterization reveals that the highly luminescent, strongly Stokes‐shifted broadband emission of 0D Cs3 Cu2 I5 NCs arises from the self‐trapped excitons. Our findings not only present a method to control the synthesis of low‐dimensional cesium copper halide nanocrystals but also highlight the potential of 0D Cs3 Cu2 I5 NCs in optoelectronics. Abstract : Aufwärmübung : Mit denselben Reaktanten und Liganden, aber unterschiedlichen Reaktionstemperaturen können sowohl 1D‐CsCu2 I3 ‐Nanostäbchen (NRs) als auch 0D‐Cs3 Cu2 I5 ‐Nanokristalle (NCs) synthetisiert werden. Die reduzierte Dimensionalität von Cs3 Cu2 I5 (0D) im Vergleich zu CsCu2 I3 (1D) sorgt für eine erhöhte Lokalisierung von Excitonen, wodurch die Cs3 Cu2 I5 ‐NCs eine stärkere Emission zeigen.